Four kinds of fallacies in comparing market-type and Soviet-type economies: issues and outcomes - J. WINIECKI (PSL Quarterly Review, 2013)
The work highlights the most common fallacies in comparing market-type and Soviet-type economies. The author analyses four kinds of fallacy that tend to reduce - for different reasons and in different ways - the development differential  between mature industrialised market-type economies and Soviet-type ones. As each of the fallacies in question skews comparisons in the same direction, their cumulative effect is substantial.  It is argues that the fallacies are at the root of many overestimates of Soviet development and of the even more frequent confusion resulting from the conflict between eyewitness and other unquantified unofficial evidence and official estimates.